2021
DOI: 10.5194/gmd-14-1699-2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transient processes for thermal simulations of the Central European Basin

Abstract: Abstract. Transient processes play a major role in geophysical applications. In this paper, we quantify the significant influence arising from transient processes for conductive heat transfer problems for sedimentary basin systems. We demonstrate how the thermal properties are affected when changing the system from a stationary to a non-stationary (transient) state and what impact time-dependent boundary conditions (as derived from paleoclimate information) have on the system's overall response. Furthermore, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This can be further highlighted by looking at the intrusive counterpart of the method. Degen and Cacace (2021) show, that the results of the sensitivity analysis are not impacted by the model accuracy, which demonstrates that the general characteristic is the same for all models.…”
Section: Requirement 4: Robustnessmentioning
confidence: 57%
See 2 more Smart Citations
“…This can be further highlighted by looking at the intrusive counterpart of the method. Degen and Cacace (2021) show, that the results of the sensitivity analysis are not impacted by the model accuracy, which demonstrates that the general characteristic is the same for all models.…”
Section: Requirement 4: Robustnessmentioning
confidence: 57%
“…The non-intrusive RB method maintains the input-output relationship, in contrast to, for instance, PINNs. As shown for its intrusive counterpart, the results of a sensitivity analysis do not change significantly with the surrogate model accuracy (Degen and Cacace, 2021), demonstrating that the surrogate does not change the general characteristics of the original problem and making it a suitable technique to ensure the feasibility of global sensitivity studies also for large-scale models.…”
Section: Challenge 1: Sensitivity Analysismentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, we could, for instance, employ a Robin boundary condition to allow an interaction between the subsurface and the atmosphere. A previous study 38 has shown that a variation of the value of the boundary condition does not majorly impact the sensitivities of the model response as long as we consider a Dirichlet boundary condition. This is the reason because the value of the boundary condition is the same in every realization.…”
Section: Uncertainty Quantification Mapsmentioning
confidence: 94%